French Language Learning Media Based on Project-Based Learning Assisted by the Pear Deck Application - Zudya Pratidina; Mukhtar Mukhtar; Naeklan Simbolon (Randwick International of Education and Linguistics Science Journal, 2024)
The purpose of this research is to determine (1) the feasibility of learning media assisted by the Pear Deck application based on project-based learning (PjBL). (2) determine the effectiveness of PjBL-based learning media. The research method is R&D using the Borg and Gall development models. This research was conducted in class XI SMAN 1 Lubuk Pakam, totaling 28 students. The research subjects are material experts, media experts, and design experts. The research results show that: (1) the learning material expert test criteria are very good (94%); (2) the learning media expert test criteria are very good (93%); and (3) the learning design expert test criteria are very good (94%). The results of submitting a hypothesis can prove that: (1) learning media assisted by the PjBL-based Pear Deck application is suitable for use (2) The learning media assisted by the PjBL-based Pear Deck application is effective to use. The average effectiveness of students' French learning outcomes in using the PjBL-based Pear Deck Application in the experiment class was 86.42%, and the average effectiveness of the average effectiveness of students who used picture and book learning media in the control class was 49.5%. The posttest results obtained a value of Tcount = 7.08 at a significant level of α = 0.05, with dk 27 obtaining Ttable = 1.674, so that Tcount > Ttable, namely 7.08 > 1.674. The use of learning media assisted by the PjBL-based Pear Deck application is very feasible and effective.